KEPRIBADIAN TOKOH UTAMA DALAM NOVEL BULAN TAK PURNAMA KARYA AHMAD BASRI AFANDI - Ongko; Faika Burhan; Nurmin Suriyati (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study entitled “the personality of the main shape in the Bulan Tak Purnama novel by Ahmad Basri Afandi” uses a qualitative descriptive method. The object of this research is the Bulan Tak Purnama novel by Ahmad Basri Afandi, which contains the turmoil of Dani’s personality in realizing his instincts. Among them the desire to get married, the desire to make his mother happy, love and sex. The results of this study indicate that the main shape Dani has a person who is virtuous, attention, caring, optimistic, honest, merciful and sincere. This can be proven by looking at the id, ego and superegoes. Literary psychology is a science that understands the reflection and mental activities of humans. The reflection and psychological activity of the human being is in the character of Dani as the main shape in the Bulan Tak Purnama novel by Ahmad Basri Afandi. Keywords: shape, novel, personality, literature psychology